Nonketotic Hyperglycinemia of Infants in Taiwan - Chiao-Fan Chiu; Ju-Li Lin; Jainn-Jim Lin; Min-Hua Tseng; Fu-Sung Lo; Ming-Chou Chiang (Pediatrics and Neonatology)
Nonketotic hyperglycinemia (NKH) is a rare, inherited disease, with very poor outcome. It is difficult to confirm the diagnosis due to nonspecific presentations and rapid progression. The incidence was reported in a few countries. We report the clinical and genetic features of typical neonatal NKH with novel splicing mutation, c.1058+3A>C, in the intron 7 of the glycine decarboxylase (GLDC) gene. Furthermore, this study aimed to delineate the estimated incidence and clinical characteristics of NKH in the Taiwanese population. Methods: Reports of Health Promotion Administration, Ministry of Health and Welfare of Taiwan, during the period from 2000 to 2013; the Human Gene Mutation Database; and literature regarding NKH in Taiwan were reviewed. Demographic information, age of onset, clinical characteristics, genetic analysis, electroencephalography examinations, and outcome of the patients were analyzed. Results: The estimated incidence of NKH in the Taiwanese population was 7.2 cases per 1,000,000 live births. Among the 12 cases reported in Taiwan, more than 90% were of neonatal type. Fifty-five percent of affected patients died within 5 years, and all survivors had severe neurologic outcomes. Only three infants underwent genetic analysis during the study period. Two neonatal NKH infants had mutation in the GLDC gene, and the other one, who had late-onset NKH, had mutation in the glutaredoxin 5 gene. Conclusion: Compared with other countries, the estimated incidence of NKH was relatively rare in the Taiwanese population. It is important to characterize all index cases at the genetic level. With more awareness of NKH, increased knowledge of gene mutation, and improvement of diagnostic tools, NKH can be diagnosed more accurately.